Dissociating the effects of similarity, salience, and top-down processes in search for linearly separable size targets. - Hodsoll, J; Humphreys, G; Braithwaite, J (2006)
In two experiments, we explored the role of foreknowledge on visual search for targets defined along the size continuum. Targets were of large, medium, or small size and of high or low similarity relative to the distractors. In Experiment 1, we compared search for known and unknown singleton feature targets as a function of their size and similarity to the distractors. When distractor similarity was high, target foreknowledge benefited targets at the end of the size continuum (i.e., large and small) relatively more than targets of medium size. In Experiment 2, participants were given foreknowledge of what the target was not The beneficial effect of foreknowledge for endpoint targets was reduced. The data indicate the role of top-down templates in search, which can be "tuned" more effectively for targets at the ends of feature dimensions.